Hubungan antara Minat Siswa terhadap Prestasi Belajar pada Mata Pelajaran Sejarah Kebudayaan Islam di MAN Kotabaru - Herni Aliska (Lembaga Anotero Scientific Pekanbaru, 2025)
This study was motivated by the importance of Islamic Cultural History (SKI) in shaping students' understanding and character through emulating Islamic historical values. However, student achievement is often influenced by affective factors, particularly learning interest, which determines their involvement in the learning process. The purpose of this study was to determine the level of student interest in SKI, measure their learning achievement, and analyze the relationship between the two. This study used a quantitative approach with a correlational descriptive method, involving 263 students from MAN Kotabaru as samples. Data were collected through questionnaires, observations, interviews, and documentation of achievement scores, then analyzed using the product moment correlation technique. The results showed that students' interest in SKI was in the high category, with average learning achievement also in the high category. Correlation analysis found a strong and significant relationship between interest and learning achievement, meaning that the higher the students' interest, the better their academic achievement. In conclusion, learning interest proved to play an important role in improving SKI achievement, so teachers need to design learning strategies that can maintain and increase student interest. This study provides theoretical implications for the development of Islamic education studies as well as practical implications for improving learning methods in madrasahs.